Carbon fiber composites with battery function: Stresses and dimensional changes due to Li-ion diffusion. (August 2018) - Xu, Johanna; Lindbergh, Göran; Varna, Janis
Structural composite materials that simultaneously carry mechanical loads, while storing electrical energy offers the potential of significantly reduced total component weight owing to the multifunctionality. In the suggested micro-battery, the carbon fiber is employed as a negative electrode of the battery and also as a composite reinforcement material. It is coated with a solid polymer electrolyte working as an ion conductor and separator while transferring mechanical loads. The coated fiber is surrounded by a conductive positive electrode material matrix. This paper demonstrates a computational methodology for addressing mechanical stresses arising in a conceptualized micro-battery and dimensional changes of the cell during electrochemical cycling, caused by time-dependent gradients in lithium ion concentration distribution.